Climate Change as Ecological Colonialism: Dilemma of Innocent Victims - Upadhyay, Prakash (Himalayan Journal of Sociology and Anthropology, 2017)
Climate Change is at just the once a social, cultural and an ecological issue. It is an environmental justice issue, an issue of economic and political domination, a consequence of clash between deregulated capitalism and the welfare of mankind deeply entrenched in a capitalist economic system based upon the persistent exploitation of natural resource for individual benefits. Poverty stricken peoples of least developed countries are the innocent victims of climate change. This article argues and identifies key ways that anthropological knowledge/lens can enrich and deepen contemporary understandings of climate change. From discussions allied to natural resource management practices it is construed that natural resource management practices are impacted from factors –political, economic (capitalism), domination, cultural, community and societal activities which are anthropogenic factors responsible for climate change calling for the equity and justice implications of climate change issues. As climate change is ecological colonialism at its fullest development-its critical scale-with sweeping social, cultural, economic and political implications, anthropological lens seek to respond to climate change at the local, regional, national, and global scales and are helpful in reflecting the understandings in application and seeking ways to pool resource with communities to assist them in addressing their climate change concerns. There are some other key contributions that anthropology can bring to understandings of climate change viz. awareness of cultural values and political relations that shape the production and interpretation of climate change knowledge, survival, power, ethics, morals, environmental costs and justice, militarism, war, intertwined crises of food, water, biodiversity loss and livelihood. Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 111-140